The Influence of Classical Learning and Learning Motivation on Learning Outcomes in the Study of IPAS for Students of Class VI SDN 13 Benteng Mandalle Sub-District Pangkep District - B, Santi; Yunus, Muh; Nurdin, Nurdin (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This research is a descriptive quantitative research. The objectives of this study are to: (1) Explain the effect of Classical Learning on learning outcomes (2) Explain the effect of Learning Motivation on learning outcomes. (3) Explain the effect of Classical Learning and Learning Motivation on student learning outcomes. Data collection using questionnaires, documents and observations. The research method used is quantitative research, the tools used are questionnaires and documents. The population of this study were grade VI students of SDN 13 Benteng Pangkep Regency with a sample size of 10 people. In analyzing the data used in this study, multiple regression analysis, determination, t-test and f-test were used. (1) Classical learning contributes to learning outcomes. (2) Learning motivation contributes to learning outcomes. (3) Classical learning and learning motivation affect student learning outcomes.